Knowledge-focused marketing strategy implementation model for an internet service provider : a case study on Telekom Multimedia - Maarof, Faridah (2003)
This study focuses on improving the current marketing exercise in the internet service provider business. The case study refers to one of the leading internet service provider, Telekom MultimeQa. The problem faced was the ineffective implementation of the marketing strategy. The goal of h s project is to recommend a knowledge focused marketing strategy implementation model (k-marketing strategy implementation model) supported by a practical organizational design for the internet service. The objectives supporting the goal of this project are as follows: (a) to acquire knowledge on the customers' distribution and demand, customers' attitudes, usage pattern, customers' perception and satisfaction level, (b) to acquire knowledge and understanding of the current business process to recommend a better practice through knowledge creation and development, (c) to introduce a knowledge tool in the current business practice in identifling customers distribution and demand and (d) to develop a knowledge focused marketing strategy implementation model to improve the business process in acheving the business objectives. The scope of the study encompasses the identification of the prior components of a marketing strategy of the TMnet 15 15 service for the residential group. The action research approach engaged in this study is supported by the core elements of knowledge management: knowledge acquisition, knowledge creation, knowledge development and knowledge preservation. The research methods used are surveys, comparative study and case study. The outputs of h s study are as follows: recommendation of the customer-focused marketing activities that assist the internet service provider in achieving its objectives, and a knowledge focused marketing strategy implementation model supported by the proposed organizational structure concept in ensuring the achevement of a competitive edge. The benefit obtained from ths study is the improvement of the business practice, whch has led to the improvement in the revenue performance of TMnet 15 15 service.